Respostas

2013-11-27T11:36:02-02:00
A) 14  - 12  + 7  =
    5      3     10               mmc 5,3,10 =30

84  - 120  + 21 =  105 - 120  = -  15     =  - 1
        30                   30              30          2


b) 4 - 1  = 
         7                      mmc = 7

  28 - 1  =  27   
    7          7


c)  11   + 2 - 9 =                  mmc = 10,2 = 10
     2           10

   55 + 20 - 9 =  75 - 9  = 66   =  6,6 
       10            10           10
2013-11-27T12:05:09-02:00
A)
4 - 1 2 +  7      
   5     3     10        
9 - 5 + 
5   3   10
mmc (5, 3, 10) = 30     
54 - 50 + 21 =  25 = 5
       30            30    6


b)
4 -  = mmc = 7
     7 
28 - 1 = 27 = 3 6
       7     7       7

c) 
1 1 + 2 -  9  =
   2        10       
  3 + 2 -  9  
  2        10   
mmc (2, 10) = 10
15 + 20 - 9 = 26 = 2 3
     10           10       5

d)
7 2 - 2 5
   3      6
23 - 17 =
 3     6
mmc (3, 6) = 6
46 - 17 =
    6
29 = 4 5
 6        6